Professional Support in Teaching Mathematics through Guided Discovery: The Role of Agency on Multiple Levels - Péter Juhász; Réka Szász; Gábor Szűcs; Eszter Varga (MDPI AG, 2024)
The paper describes a case study of mentoring support provided to a novice mathematics teacher in using Guided Discovery in her classroom. The study used qualitative methods: thematic analysis of interviews and discussions. A central theme that emerged in the results was agency, and we observed that the high level of student and teacher agency in Guided Discovery results in the importance of teacher agency within and over the mentoring framework. We conclude that when supporting teachers in using Guided Discovery in their mathematics classrooms, teacher educators need to put an increased focus on teacher agency within and over the mentoring process.